Psychometric analysis: Differences in person and item reliability on the adaptation of the Islamic school environment instrument in Indonesia - Mujiansyah, Mujiansyah; Ridwan, Achmad; Rahmawati, Yuli (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyze person and item reliability in the adaptation of an Islamic school environment instrument in Indonesia, as well as evaluate its psychometric quality. The study was conducted at SMAIT Ukhuwah Banjarmasin, involving 80 11th-grade students. The adapted instrument covers dimensions of the physical environment, Islamic foundations, and interaction values in learning. Analysis using the Rasch model shows good overall psychometric properties. Person and item reliability reached 0.97, categorized as "excellent". Infit and Outfit MNSQ values are within an acceptable range, indicating a good fit between data and the model. Unidimensionality analysis yielded a raw variance explained by measures value of 58.5%, indicating the instrument is quite good at measuring a single construct. However, several items were identified as misfit with the Rasch model, indicating the need for revision. High separation values for person (6.13) and item (5.31) demonstrate the instrument’s ability to distinguish various trait levels. The results of this study provide a strong foundation for the development and refinement of Islamic school environment measurement instruments in Indonesia.